The Development and Validation of a Dehumanization Measure Within Romantic Relationships - Pizzirani, Bengianni; Karantzas, Gery C.; Mullins, Ellie R. (Frontiers in Psychology, 2019)
Despite the emergence of research into interpersonal dehumanization, there has been little by way of empirical investigation of the phenomenon within the context of romantic relationships. To address this, we introduce and validate the Dehumanization in Romantic Relationships Scale (DIRRS), a self-report measure of dehumanization perpetration and targeting within close relationships. In Study 1 (N=1251, M age=25.35, SD=6.03), confirmatory factor analysis revealed that the dimensionality of interpersonal dehumanization may be more nuanced than first thought. Specifically, a four factor first-order structure (comprised of factors that relate to denials of human uniqueness [i.e., immature and unrefined] and human nature [i.e., exploitable and emotionless] was found to be the best fit to the data. These results were replicated on a different sample in Study 2 (N=847, M age=3.55 years, SD=4.27)—in addition to the assessment of criterion-related validity. Study 3 (N=328, M age=2.40 years, SD=4.27) cross-validated the criterion-related validity reported in Study 2, and in addition, highlights that dehumanization is also associated with emotional and physical abuse. This research extends theory on interpersonal dehumanization and provides an empirically validated measure to reliably assess the occurrence of dehumanization within romantic relationships